2018
DOI: 10.1021/acs.nanolett.8b00515
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stressing Induced Monolayer Vacancy Island Growth on TiSe2

Abstract: To ensure practical applications of atomically thin transition metal dichalcogenides, it is essential to characterize their structural stability under external stimuli such as electric fields and currents. Using vacancy monolayer islands on TiSe surfaces as a model system, we have observed nonlinear area evolution and growth from triangular to hexagonal driven by scanning tunneling microscopy (STM) subjected electrical stressing. The observed growth dynamics represent a 2D departure from the linear area growth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…A highresolution STM topographic image of a defect-free 1T-PtSe 2 surface is shown in figure 1(c). Similar to previous STM study on monolayer PtSe 2 grown though selenization of a Pt(1 1 1) substrate and other transition-metal diselenides [2,59], the hexagonal protrusions in figure 1(c) represent the topmost Se atoms. From the arrangement of the surface Se atoms, the in-plane lattice constant of 1T-PtSe 2 is determined to be 0.375 ± 0.003 nm, which is consistent with previous theoretical and experimental results [2,17,60].…”
Section: Stm Topographic Imagessupporting
confidence: 69%
See 3 more Smart Citations
“…A highresolution STM topographic image of a defect-free 1T-PtSe 2 surface is shown in figure 1(c). Similar to previous STM study on monolayer PtSe 2 grown though selenization of a Pt(1 1 1) substrate and other transition-metal diselenides [2,59], the hexagonal protrusions in figure 1(c) represent the topmost Se atoms. From the arrangement of the surface Se atoms, the in-plane lattice constant of 1T-PtSe 2 is determined to be 0.375 ± 0.003 nm, which is consistent with previous theoretical and experimental results [2,17,60].…”
Section: Stm Topographic Imagessupporting
confidence: 69%
“…Similar to previous STM study on monolayer PtSe2 grown though selenization of a Pt(111) substrate and other transitionmetal diselenides, the hexagonal protrusions in FIG. 1c represent the topmost Se atoms [2,58].…”
Section: A Stm Topographic Imagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Scanning tunneling microscopy (STM) has been used to examine single crystal surfaces and revealed that structural defects, such as vacancies, substitutional or interstitial impurities, are regions of absorptive binding for gases and ions; therefore, they are considered active sites for catalysis [137][138][139]. For example, as shown in Fig.…”
Section: Scanning Tunneling Microscopymentioning
confidence: 99%